Pengaruh Struktur Modal, Tingkat Pertumbuhan, Ukuran Perusahaan terhadap Kebijakan Dividen pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di BEI Tahun 2018-2021 - Wiyono, Gendro; Rana, Odilia Yunita (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The dividend policy is a company's financial decision whether the profits earned will be distributed to shareholders or retained as retained earnings to finance future investments. Dividend policy often creates conflict between company management and shareholders. This study aims to examine the effect of capital structure, growth rate, company size on dividend policy in consumer goods industry sector companies listed on the IDX in 2018-2021. Which will be used as samples in this study, namely as many as 18 companies. In this study, the capital structure is proxied using the Debt to equity ratio (DER), the growth rate is proxied by total asset growth (Growth), and company size is proxied by log of total assets (Size). Proposive sampling method is the method used as a determinant of this research sample. The analytical method used is descriptive test, classical assumption test and multiple linear regression analysis using the SPSS application. The results of this study indicate that capital structure has a negative effect on dividend policy, company growth and company size have a positive effect on dividend policy. Keywords: Capital Structure, Growth Rate, Company Size, Dividend Policy